1993
DOI: 10.1063/1.464540
|View full text |Cite
|
Sign up to set email alerts
|

Crossed beam studies of four-atom reactions: The dynamics of OH+CO

Abstract: The angular and velocity distribution of CO2 product from the reaction OH+CO at 14.1 kcal/mole collision energy has been obtained in a crossed molecular beam study. The reaction is found to proceed through an osculating HOCO complex living about one rotational period. About 65% of the available energy goes into product translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
90
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 51 publications
4
90
0
Order By: Relevance
“…Gas phase and theoretical studies predict a three-stage barrier (∼500 K; e.g., Frost et al 1993;Yu et al 2001). The reaction proceeds via an energetic HOCO intermediate, which isomerizes from trans-HOCO to cis-HOCO, before dissociating to form CO 2 (Smith & Zellner 1973;Alagia et al 1993;Lester et al 2000). Lester et al (2001) suggest that a precursor OH-CO complex forms prior to the HOCO intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…Gas phase and theoretical studies predict a three-stage barrier (∼500 K; e.g., Frost et al 1993;Yu et al 2001). The reaction proceeds via an energetic HOCO intermediate, which isomerizes from trans-HOCO to cis-HOCO, before dissociating to form CO 2 (Smith & Zellner 1973;Alagia et al 1993;Lester et al 2000). Lester et al (2001) suggest that a precursor OH-CO complex forms prior to the HOCO intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…2 Kinetic studies have revealed that its rate constant is essentially flat at low temperatures but increases quickly with T above 500 K. [3][4][5] This behavior has been attributed to a complexforming mechanism, 6 although the lifetime of the HOCO intermediate is not particularly long. 7,8 Molecular beam experiments on the title reaction 9 and its reverse 10 suggested complex reaction dynamics with a significant non-statistical component. In addition, significant tunneling towards H + CO 2 has been observed in photodetachment of the HOCO − anion.…”
mentioning
confidence: 99%
“…[2][3][4] As a four-atom system, the OH + CO → HOCO → H + CO 2 reaction is amenable to a broad range of theoretical treatments, 2, 5-8 and several high-level potential energy surfaces (PESs) exist. [9][10][11][12][13] The reaction proceeds through the strongly bound cis-HOCO intermediate 14 and shows striking non-Arrhenius behavior. 3 The exact height and shape of the barrier to the formation of H + CO 2 are critical to the overall kinetics of the reaction.…”
mentioning
confidence: 99%